Plumeria species: a review of morphology, traditional uses, phytochemicals, and pharmacological activities - Bruna da Silva Souza; Ana Clara Silva Sales
Plants from genus Plumeria belong to the Apocynaceae family and are considered native to the New World. These plants are commonly found in tropical and subtropical areas around the world. Plumerias are well known for their ornamental value and especially as medicinal agents. Species from this genus have played a crucial role in the popular herbal medicine as well as in alternative and complementary system of medicine. This review collects and updates information about Plumeria species. The article highlights findings and explores the medicinal status of these plants with their biological properties and phytochemical components suggested by describing several studies with in vitro and in vivo evaluations. Our review emphasizes the potential beneficial effects of Plumerias for human and provides evidence that this genus can be used as source for drug development in future